Transport of Antarctic stratospheric strongly dehydrated air into the troposphere observed during the HALO-ESMVal campaign 2012 - Rolf, C.; Afchine, A.; Schlager, H.; Spelten, N.; Sumińska-Ebersoldt, O.; Ungermann, Jörn; Zahn, A.; Krämer, M.; Bozem, H.; Buchholz, B.; Ebert, V.; Guggenmoser, T.; et al. (EGU, 2015)
Dehydration in the Antarctic winter stratosphere is a well-known phenomenon that is occasionally observed by balloon-borne and satellite measurements. However, in-situ measurements of dehydration in the Antarctic vortex are very rare. Here, we present detailed observations with the in-situ and GLORIA remote sensing instrument payload aboard the new German aircraft HALO. Strongly dehydrated air masses down to 1.6 ppmv of water vapor were observed as far north as 47° S and between 12 and 13 km in altitude, which has never been observed by satellites. The dehydration can be traced back to individual ice formation events, where ice crystals sedimented out and water vapor was irreversibly removed. Within these dehydrated stratospheric air masses, filaments of moister air reaching down to the tropopause are detected with the high resolution limb sounder, GLORIA. Furthermore, dehydrated air masses are observed with GLORIA in the Antarctic troposphere down to 7 km. With the help of a backward trajectory analysis, a tropospheric origin of the moist filaments in the vortex can be identified, while the dry air masses in the troposphere have stratospheric origins. The transport pathways of Antarctic stratosphere/troposphere exchange are investigated and the irrelevant role of the Antarctic thermal tropopause as a transport barrier is confirmed. Further, it is shown that the exchange process can be attributed to several successive Rossby wave events in combination with an isentropic interchange of air masses across the weak tropopause and subsequent subsidence due to radiative cooling. Once transported to the troposphere, air masses with stratospheric origin are able to reach near-surface levels within 1–2 months.